The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1111/1540-8520.00030
|View full text |Cite
|
Sign up to set email alerts
|

The Entrepreneurial Personality in the Context of Resources, Environment, and the Startup Process—A Configurational Approach

Abstract: The goal of this interdisciplinary study is to analyze the entrepreneurial personality in the context of resources, environment, and the startup process based on a configurational approach. The study focuses on the startup process. A questionnaire was developed to measure the configuration areas of personality, personal resources, environment, and organizing activities. A representative sample of 1,169 nascent entrepreneurs and new business owner-managers was examined. Three startup configurations were found w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
218
1
33

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(273 citation statements)
references
References 47 publications
7
218
1
33
Order By: Relevance
“…Many researchers have found that a high need for achievement predicts entry into entrepreneurship, although this finding is sometimes challenged in specific contexts. Among the settings discussed above, the higher need for achievement is evident in the studies of the Austrian entrepreneurs (Korunka et al, 2003) and the Turkish students (Gürol and Atsan, 2006), but not in the study of Swedish entrepreneurship students (Hansemark, 2003). Comparing four Austrian studies, Frank et al (2007) conclude that the need for achievement selects individuals for entry into entrepreneurship.…”
Section: Need For Achievementmentioning
confidence: 98%
See 2 more Smart Citations
“…Many researchers have found that a high need for achievement predicts entry into entrepreneurship, although this finding is sometimes challenged in specific contexts. Among the settings discussed above, the higher need for achievement is evident in the studies of the Austrian entrepreneurs (Korunka et al, 2003) and the Turkish students (Gürol and Atsan, 2006), but not in the study of Swedish entrepreneurship students (Hansemark, 2003). Comparing four Austrian studies, Frank et al (2007) conclude that the need for achievement selects individuals for entry into entrepreneurship.…”
Section: Need For Achievementmentioning
confidence: 98%
“…This echoes earlier findings by Evans and Leighton (1989), and many studies find parallel results. In a cross-sectional study, Korunka et al (2003) measure that Austrian entrepreneurs (defined as "successful new owner-managers") have a strong internal LOC compared to "nascent entrepreneurs." Gürol and Atsan (2006) find that Turkish students who are more entrepreneurially inclined have a higher LOC.…”
Section: Locus Of Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers of entrepreneurship classes tend to center their instruction on teaching students to "think outside the box" or to "color outside the lines" since most believe these actions will lead to success in the entrepreneurial context. Researchers explore how entrepreneurs are different from others in terms of their knowledge , personality (Korunka et al 2003), motivation (Naffziger et al 1994), and cognition . Given our interest in difference as being essential to entrepreneurial behavior and action (and constituting the basis for entrepreneurs' fulfillment of their distinctiveness needs), it is crucial to concurrently think about existing studies suggesting that when individuals distinguish themselves as entrepreneurs, they may not be fulfilling their belongingness needs.…”
Section: The Identity Distinctiveness Of Entrepreneurial Individualsmentioning
confidence: 99%
“…Teachers of entrepreneurship classes tend to center their instruction on teaching students to "think outside the box" or to "color outside the lines" since most believe these actions will lead to success in the entrepreneurial context. Researchers explore how entrepreneurs are different from others in terms of their knowledge (Shane 2000), personality (Korunka et al 2003), motivation (Naffziger et al 1994), and cognition (Busenitz and Barney 1997). Given our interest in difference as being essential to entrepreneurial behavior and action (and constituting the basis for entrepreneurs' fulfillment of their distinctiveness needs), it is crucial to concurrently think about existing studies suggesting that when individuals distinguish themselves as entrepreneurs, they may not be fulfilling their belongingness needs.…”
Section: The Identity Distinctiveness Of Entrepreneurial Individualsmentioning
confidence: 99%